REVITALISASI NILAI RELIGIUS GENERASI MUDA MELALUI TRADISI AL-BARZANJI - Fauziah, Euis Naelah (Prodi Pendidikan Agama Islam IAINU Kebumen, 2025)
The purpose of this study was to determine the religious values contained in the Al- Barzanji book, which are instilled in the NU Fatayat in Sidomoro Village. Furthermore, it was also to determine the strategies used to instill these religious values. The research method used was a qualitative approach with a case study. Data collection was conducted through interviews, observation, and documentation involving NU Fatayat administrators and members of the NU Fatayat in Sidomoro Village, Buluspesantren, Kebumen. The results showed that the Al-Barzanji reading activity was carried out routinely every third week of the month. Through this activity, the religious values instilled were aqidah (faith), moral values in social interactions, moral values towards children, gratitude, politeness, and compassion. The strategies used to instill religious values included role modeling, habituation, advice, reciting the Al-Promise book with beautiful melodies and understanding its meaning, and giving individual reading assignments.